2019
DOI: 10.1021/acs.estlett.9b00142
|View full text |Cite
|
Sign up to set email alerts
|

Allantoin as a Marker of Oxidative Stress: Inter- and Intraindividual Variability in Urinary Concentrations in Healthy Individuals

Abstract: Altered systemic oxidative stress is a consequence of environmental exposures and diseases, among other stress factors. The extent of oxidative stress in humans is assessed through the analysis of oxidative stress biomarkers (OSBs) in biospecimens such as urine. Allantoin is an OSB, a specific product of the oxidation of uric acid, that is measurable in urine. In this study, concentrations and inter-and intraindividual variability in urinary concentrations of allantoin were determined in healthy individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…A key finding in this study is that salivary allantoin was shown to be a potential indicator of IMT and cardiometabolic risk in patients with type 2 diabetes. Allantoin, produced by oxidation of urate, has been proposed as a biomarker for oxidative stress ( Martinez-Moral and Kannan, 2019 ), while other studies have shown that urinary excretion of allantoin is correlated with atherosclerosis extension in mice ( Li et al, 2015 ) and plasma allantoin is correlated with carotid atherosclerosis in humans ( Santana et al, 2018 ). This is the first investigation to find an association between carotid atherosclerosis and salivary allantoin.…”
Section: Discussionmentioning
confidence: 99%
“…A key finding in this study is that salivary allantoin was shown to be a potential indicator of IMT and cardiometabolic risk in patients with type 2 diabetes. Allantoin, produced by oxidation of urate, has been proposed as a biomarker for oxidative stress ( Martinez-Moral and Kannan, 2019 ), while other studies have shown that urinary excretion of allantoin is correlated with atherosclerosis extension in mice ( Li et al, 2015 ) and plasma allantoin is correlated with carotid atherosclerosis in humans ( Santana et al, 2018 ). This is the first investigation to find an association between carotid atherosclerosis and salivary allantoin.…”
Section: Discussionmentioning
confidence: 99%
“…The MSRA for pantothenate in rice bran-fed infants was similar throughout the study months, whereas control infants showed fluctuations. For pyridoxine, the MSRA in rice bran-fed infants steadily Hypoxanthine and xanthine are precursors of uric acid, a powerful antioxidant, and allantoin is a product of uric acid oxidation and an oxidative stress biomarker [38]. Compared to control infants, hypoxanthine and xanthine MSRA were higher in rice bran-fed infants from months 7 to 10.…”
Section: Dbs Vitamin and Co-factor Moleculesmentioning
confidence: 90%
“…Allantoin was quantified using LC-MS/ MS as described )Agilent 1200 series HPLC system and Agilent G6460, Agilent Technologies, Santa Clara, CA, USA(. 11 Each 50 μl aliquot of urine was added to 50 μl 1 μg/ml Allantoin- 13 77)59( 52.5)57( 0.0251 Continuous data are mean±SD, median )IQR(. *P-value for patients between three groups.…”
Section: Liquid Chromatography Tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%
“…[25][26][27][28] Among these products, allantoin is the most stable product and is considered a good oxidative reactions biomarker in the human body. 11 In this study, we examined allantoin production. Both 24-hour excretion of allantoin and allantoin/UCr were significantly decreased in patients with TBI after normalization with urine creatine to minimize renal secretion effects.…”
Section: Renal Filtration and Reabsorption Assessmentmentioning
confidence: 99%